Genetic Diversity, Biofilm Formation, and Antibiotic Resistance in Listeria monocytogenes Isolated from Meat-Processing Plants - Miguel Romeo; Amaia Lasagabaster; María Lavilla; Félix Amárita (Foods)
Listeria species are ubiquitous microorganisms that can be present all over the food chain. They can survive under adverse conditions and are frequently found in food-processing plants. In this study, 19 Listeria innocua and 19 Listeria welshimeri strains were isolated from meat product manufacturing companies in Spain, and biofilm formation capabilities were analyzed. In addition, 37 Listeria monocytogenes strains were also isolated, and their genetic diversity, biofilm formation capabilities, and antibiotic resistance were analyzed too. The species distribution was similar between two food-processing plants in the Basque Country, while it demonstrated significant variation when compared to three other plants from the Valencian Community, Catalonia, and Andalusia. Biofilm formation was significant at both 25 °C and 37 °C, with L. monocytogenes showing strong biofilm formation capabilities. Biofilms enhance the ability of bacteria to persist on surfaces and equipment. Listeria monocytogenes serogroup analysis indicated significant differences between Basque Country strains and those from the other regions, with most strains belonging to serogroups commonly associated with human listeriosis cases. Antibiotic multi-resistance was a common feature among L. monocytogenes strains. The presence of different antibiotic multi-resistance profiles and strong biofilm-forming capabilities highlights the importance of stringent hygiene and monitoring practices to prevent the spread of L. monocytogenes in the food chain and avoid food-safety threats and public-health issues.